Dilemmas in social work field education : decision cases - Wolfer, Terry A.; Reitmeier, Melissa Catherine (Columbia University Press, 2021)
"Since 2008, the Council on Social Work Education has identified field education as the social work profession's signature pedagogy. The success of field education depends heavily on field educators-field instructors, task supervisors or preceptors, and faculty field liaisons-for delivering a competency-based learning experience for students and maintaining the pedagogical integrity of the field practicum experience. Despite this focus on field education from the national organization and its accreditation standards, little guidance or resources for empirically based methods exist to orient field educators. In this anthology of decision cases (which require discussants to formulate the problem portrayed and decide on the best course of action), Wolfer and Reitmeier present fourteen cases of actual experiences of field instructors, faculty field liaisons, and field students. These detailed narratives based on in-depth interviews showcase the complex, messy dynamics of field education and highlight a range of issues experienced by novice and seasoned field educators that will increase their supervisory competence and confidence"--